Effects of biogas and raw slurries on grass growth and soil microbial indices. Issue 2 (1st February 2016) - Wentzel, Stefanie; Joergensen, Rainer Georg
Abstract: Biogas slurry is increasingly used as fertilizer. Earlier research was focused on plant growth and soil chemical properties, with only little information available regarding the effects of biogas slurry on soil and root microbial indices. For this reason, a 70 d pot experiment was conducted in which biogas and raw slurries obtained from six biodynamic farms were added to a soil. Italian ryegrass ( Lolium multiflorum Lam.) was cultivated to investigate the effects on plant yield, N uptake (two harvests), soil microbial biomass, soil fungi, and root‐colonizing microorganisms. Biogas slurries increased the mean total above‐ground plant biomass by 66% and raw slurries by 35% in comparison to the control. The mean plant N‐uptake increased under biogas and raw slurry application by 166% and 65%, respectively, compared with the unfertilized pots. The effects of biogas and raw slurry application on soil microbial indices were similar except for the lower fungal biomass after biogas slurry amendment. In contrast to biogas slurries, the raw slurries significantly increased microbial biomass C and N by roughly 25% in comparison to the control. The application of biogas slurries significantly decreased the soil ergosterol content in comparison with raw slurry and control treatment, leading to a significantly lower ergosterol : microbial biomass C ratio. In the roots, biogas and raw slurry application significantly decreased the concentrations of the amino sugars galactosamine and glucosamine by 39 and 27%, respectively, but not that of ergosterol in comparison with the control. This was most likely due to a reduced colonization with arbuscular mycorrhizal fungi in the presence of highly available plant nutrients.